Causes and Effects of Delays in Road Construction Projects in Sudan (University of Khartoum Engineering Journal, 2023)
Construction delay is one of the serious concerns of the road industry in Sudan. The study aims to identify the causes of delays that have adverse effects on road projects in terms of time, cost and quality. Literature of different types of delays, their causes and effects on road construction projects were intensively reviewed. The study identified a number of causes of delays at great risk and have adverse effects on construction of road projects. A questionnaire based on 15 causes and 5 effects was sent to the clients, consultants and contractors. The collected data were analysed using the Relative Importance Index (RII). The results showed that the contractor is most commonly responsible for project delay (37%), followed by the client (33%) and the consultant (30%). The study findings reveal that the top five main delay causes are payment delay by client, funding problems, conflicts among the project parties, suspension of work due to the client or consultant, and project schedule changes. On the other hand, cost and time overrun, poor quality of work due to rush, and disputes are the main effects of delays. The study concluded that adequate construction budget and payments on time should be the main factors for the project success.